Internalisasi Budaya Pesantren dalam Penguatan Karakter Santri Pondok Pesantren ICBB Yogyakarta - Qiyadah Robbaniyah; Roidah Lina (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
Pesantren as an Islamic educational institution that has a dormitory system and has a role in instilling the character of students, the object of this research is at the Bin Baz Islamic Center Islamic Boarding School.  The object of this research is at the Bin Baz Islamic Center Islamic Boarding School. So the researcher is interested in doing in-depth research regarding Islamic Boarding School Cultural Relations and Santri Character Strengthening: Studies at ICBB Yogyakarta Islamic Boarding Schools. This research is a qualitative research by collecting interview data, observation and documentation. The results of this study are that cleanliness and tidiness of the dormitories in Islamic boarding schools can be achieved by understanding and carrying out several steps that must be carried out 1) understanding the function of each room, 2) identifying the needs of each room 3) designing and setting up the desired space 4) labeling and visualization management. The characters that are grown in the hostel are independent, responsible for their goods, trustworthy when given assignments, cooperate, leader, respect the opinions of others, honest, dare to think, care (towards other people/environment), disciplined, orderly, patient, agile, sensitive towards other people/environment, diligent. Cleanliness and tidiness activities and programs, namely: room pickets, daily community service in public spaces (yards, terraces, halls, mosques, etc.), mass community service, weekly community service, waste sorting, room/scan surgery, cupboard surgery, lost and found , free clothesline, barracks/auction of found items, kitchen picket, waste bank, know the environment, waste management, gardening, befoster, training on dormitory management, cleanliness competition, 5r (concise, neat, clean, caring, and diligent). The system used in the implementation of cleanliness and tidiness is a rule that is made together and implemented and monitored and evaluated by the person in charge who has been appointed by the pesantren. Habits/good habits of santri related to cleanliness, tidiness which are carried out every day and continuously will become the character of the santri in the future which will become good characters that can be implemented in any field in the future both in the world of work, when in organizations, when already married , and so forth.